Erratum: A Validation Study of a Multiple Reaction Monitoring-Based Proteomic Assay to Diagnose Breast Cancer - Kim, Yumi; Kang, Un-Beom; Kim, Sungsoo; Lee, Han-Byoel; Moon, Hyeong-Gon; Han, Wonshik; Noh, Dong-Young (Journal of breast cancer, 2020)
[This corrects the article on p. 579 in vol. 22, PMID: 31897331.].